FALSAFAH JURNALISME ISLAMI - Aliyah Nur‘aini Hanum (Khatulistiwa, 2012)
Al-Qur‘an as the foundation of Islam philosophy functions not only as a way of life in daily life of muslims but also become the basic norm of work for Muslim journalists so that it could prevent them from writing something they are not supposed to the Al-Qur‘an also encourages the emergence of normative of willingness such as the awareness of the important of writing which in turns promotes the development of Dakwah bi al-Qalam or Islamic missionary with writings. In this context, Muslim journalist are not only limited to Muslims working as journalist loyal and committed to their religious obligation. They could be Muslim scholars, preachers, clerics and Muslim (in general) who write for mass media. There are five roles of Muslim journaliststhat could be listed here; as educator (mujaddib), as corrector of wrong information (musaddid), as reformer (mujaddid), as peace-maker (muwahid) and as combatant (mujahid).